Performance comparison of the Cobas® Liat® and Cepheid® GeneXpert® systems on SARS-CoV-2 detection in nasopharyngeal swab and posterior oropharyngeal saliva. (4th May 2021) - Tsang, Hin Fung; Leung, Wai Ming Stanley; Chan, Lawrence Wing Chi; Cho, William Chi Shing; Wong, Sze Chuen Cesar
ABSTRACT: Background : Nucleic acid amplification tests (NAATs) based methods such as real-time reverse transcription polymerase-chain reaction (real-time RT-PCR) are the gold standard for diagnosis of current infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The cobas® Liat® and cepheid® GeneXpert® systems are two rapid real-time RT-PCR platforms offering rapid, specimen-to-answer detection of SARS-CoV-2. Research design and methods : In this study, we compared the performance of these two systems on SARS-CoV-2 detection in 9 nasopharyngeal swab (NPS) and 70 posterior oropharyngeal saliva specimens collected from 79 patients suspected of SARS-CoV-2 infection between August 2020 and March 2021. Results : The Positive Percent Agreement (PPA), Negative Percent Agreement (NPA) and overall Percent Agreement (OPA) between cepheid® Xpress SARS-CoV-2 assay and cobas® Liat® SARS-CoV-2 & Influenza A/B assay were found to be 100%. We demonstrated an excellent overall test concordance of the Liat® SARS-CoV-2 & Influenza A/B assay and Xpress SARS-CoV-2 assay. The small sample size of SARS-CoV-2 positive and weak-positive specimens is the inherent limitation of this study. Conclusions : The performance of the cobas® Liat® SARS-CoV-2 & Influenza A/B assay is equivalent to the cepheid® Xpress SARS-CoV-2 assay for SARS-CoV-2 detection using NPS and posterior oropharyngeal saliva.